A Life Cycle for Clusters? The Dynamics of Agglomeration, Change, and Adaption - Press, Kerstin; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2006)
The phenomenon of non-random spatial concentrations of firms in one or few related sectors (clusters) is intensively debated in economic theory and policy. The euphoria about successful clusters however neglects that historically, many thriving clusters did deteriorate into old industrial areas. This book studies the determinants of cluster survival by analyzing their adaptability to change in the economic environment. Linking theoretic knowledge with empirical observations, a simulation model (based in the N/K method) is developed, which explains when and why the cluster's architecture assists or hampers adaptability. It is found that architectures with intermediate degrees of division of labour and more collective governance forms foster adaptability. Cluster development is thus path dependent as architectures having evolved over time impact on the likelihood of future survival.
The rationale for studying cluster dynamics -- Introduction: Clusters, change and adaptation -- Literature review $1 (BThe benefits of co-location -- Stability and change: Driving cluster development -- The nature of the beast $1 (BOn the notion of agglomeration externalities -- Towards a complexity perspective on clusters -- Clusters, change and adaptation: Sticky places in slippery space? -- Modelling adaptation in clusters $1 (BThe promise of complexity theory -- Model development $1 (BClusters as complex adaptive systems -- Micromotives and macrobehaviour $1 (BDynamics of N/K systems -- Clusters as co-evolving N/K systems -- Division of labour, co-ordination and cluster adaptation -- Clusters, change and adaptation $1 (BSimulation results -- Model contribution, limitation and avenues for future research.s
Keywords: Geography; Economic geography; Statistical physics; Dynamical systems; Economic theory; Industrial organization; Regional economics; Spatial economics; Geography; Economic Geography; Regional/Spatial Science; Economic Theory/Quantitative Economics/Mathematical Methods; Industrial Organization; Statistical Physics, Dynamical Systems and Complexity; Electronic books